Becoming a sexual being: The 'elephant in the room' of adolescent brain development. (June 2017) - Suleiman, Ahna Ballonoff; Galván, Adriana; Harden, K. Paige; Dahl, Ronald E.
Highlights: Despite progress in developmental neuroscience of adolescence, there has been little focus on sexual and romantic development. Frameworks of pubertal maturation need to consider pubertal brain maturation as necessary for romantic and reproductive success. Developmental neuroscience has the potential to improve adolescent romantic, sexual, and reproductive health outcomes. Abstract: The onset of adolescence is a time of profound changes in motivation, cognition, behavior, and social relationships. Existing neurodevelopmental models have integrated our current understanding of adolescent brain development; however, there has been surprisingly little focus on the importance of adolescence as a sensitive period for romantic and sexual development. As young people enter adolescence, one of their primary tasks is to gain knowledge and experience that will allow them to take on the social roles of adults, including engaging in romantic and sexual relationships. By reviewing the relevant human and animal neurodevelopmental literature, this paper highlights how we should move beyond thinking of puberty as simply a set of somatic changes that are critical for physical reproductive maturation. Rather, puberty also involves a set of neurobiological changes that are critical forthe social, emotional, and cognitive maturation necessary for reproductive success . The primary goal of this paper is to broaden the research base and dialogue about adolescent romantic and sexual development, in hopes of advancing understanding of sex and romance as important developmental dimensions of health and well-being in adolescence.